Interaksi Simbolik Antara Wisatawan Asing dan Pedagang Lokal di Monumen Nasional Jakarta - Annisa Pratama Putri; Wibowo Irawan, Rozy Putra Pratomo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aim to analyze the Symbolic Interactions that occured between Foreigner and Local trader in Monumen Nasional Jakarta that basicly have different background of culture. This study is using the Qualitative with Case Study Method, the paradigm is Postpositivsm. Symbolic Interactions with Concept by George Herbert Mead (Mind, Self, Society) is used for this study to analyze the Symbolic Interactions between the subject. The data will be taken by Interview, Observation and Documentation Method. The result of this study is described that foreginer and Local trader Monumen Nasional Jakarta are using Verbal and Non-verbal Symbol to do communication. And this study described that the Symbolic Interactions between Foreigner and Local Trade is match with the concept that created by George Herbert Mead (Mind, Self, Society)